A colorimetric and fluorescent dual-readout probe based on red emission carbon dots for nitrite detection in meat products. (16th April 2022) - Yu, Min; Zhang, Hui; Liu, Yingnan; Zhang, Yalan; Shang, Minghui; Wang, Li; Zhuang, Yuting; Lv, Xin
Highlights: A novel fluorescent probe based on red emission carbon dots was fabricated. It was applied colorimetric and fluorometric dual-mode detection of nitrite. It had a high sensitivity and a low detection limit. It was successfully applied in detecting nitrite in meat products with satisfactory recoveries. This dual-mode probe presented great advantages for detection of nitrite in food samples. Abstract: Nitrite (NO2 – ) is widely present in the human environment and accurate, sensitive and selective detecting of nitrite is of vital significance for food safety and water quality. Herein, a novel red emission carbon dots (r-CDs) fluorescent probe was fabricated for dual-mode detection of nitrite, which was capable of both convenient colorimetric analysis and accurate fluorometric detection. When NO2 – is added to the rose-red r-CDs solution, NO2 – interacts with the amino groups which on the surface of r-CDs to form diazotized substance, resulting in that the colorimetric color of r-CDs solution realizes the transition from rose red to light purple, and the red fluorescence is gradually quenched. The detection limits of colorimetric and fluorescence for NO2 – were 0.193 μM and 0.149 μM, respectively. Furthermore, the dual-readout probe revealed satisfactory recovery and reliability when analyzing the concentration of NO2 – in ham and bacon samples..